ANALISIS RASIO AKTIVITAS DAN PROFITABILITAS UNTUK MENGUKUR KINERJA KEUANGAN PADA PT UNO SAYAP SEMESTA - Siti Hadija (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2019)
This study aims to determine the financial performance of PT Uno Wings of the Universe in terms of activity ratios and profitability ratios. The object of this research is the financial statements of PT Uno Saya Semesta period 2013-2015. Research data obtained through documentation and interview. Data analysis method used is descriptive analysis by using Trend Analysis to analyze the development of financial performance year 2013-2015 in terms of activity ratio and profitability. The results showed that the financial performance of PT Uno Wingap Semesta is viewed from the ratio of activity and profitability ratio is quite good in the period 2013 to 2014 period, but in the period 2015 the value of the ratio has decreased significantly so it can be said that the company's performance is not good in capital and asset utilization. The achievement of a declining ratio in the 2015 period is due to the improper use of receivables or receivables arising not for sales activities. Based on these results it is suggested to the management of PT Uno Wingap Semesta 1) Expected to improve the company's ability in obtaining net profit and utilize the capital and assets owned in generating profits. 2) It is expected that the assets of the company to be used for the needs of the owner outside the company's operations, should be analyzed first what impact will be generated from the use of these assets.